The judge and adhesion contracts (مجلة أبحاث قانونية, 2024)
Adhesion contracts are one of the most current topics in the legal and judicial arena at the present time. Due to the economic development that led to an economic imbalance between the two parties to the contract.It has become rare to find a contract that is free of arbitrariness in setting terms by the party with economic authority controlling the commodity or the subject of the contract. The weak party has no choice but to accept these conditions due to its need for them or because the other party is alone in supplying or producing the Commodity. It has become rare to find a contract that is free of arbitrariness in setting terms by the party with economic authority controlling the commodity or the subject of the contract. Such as insurance contracts, consumer contracts, contracts that include an exaggerated penalty clause, etc., and the weak party has no choice but to accept these conditions due to the need for them or because the other party is alone in supplying or producing the commodity.Due to the serious consequences resulting from this economic imbalance in the contract, which in turn is reflected in economic life as a whole, legal legislation did not stand idly by, but rather worked to enact legal texts that limit this encroachment and exclusivity of the strong party at the expense of the weak party. The judge was granted the authority to intervene regarding this type of contract in order to preserve the stability of contractual relations.
Keywords: contract; adhesions; judge; arbitrary terms